1980
DOI: 10.1038/clpt.1980.96
|View full text |Cite
|
Sign up to set email alerts
|

Cefotaxime kinetics after intravenous and intramuscular injection of single and multiple doses

Abstract: The kinetics of cefotaxime, a cephalosporin with an unusually broad antibacterial spectrum, were examined in humans after intravenous bolus injection, intravenous infusion every 6 hr for 14 days, and intramuscular injection every 8 hr for 10 days. Mean peak serum level after bolus injection of 500 mg was 37.9 microgram/ml; after 1 gm, 102.4 microgram/ml; and after 2 gm, 214.1 microgram/ml. The half-life (t1/2) was 1 hr for the 3 doses. Total serum clearance was the same for all doses. Overall excretion was 50%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
1
1

Year Published

1981
1981
1995
1995

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 7 publications
1
8
1
1
Order By: Relevance
“…The lower plasma and CSF levels at the end of treatment in our patients are in contrast to the data of Neu et al (17) in adults in whom serum levels after multiple dosages were shown to be predictable from single-dose studies. The reason for the lower levels in our patients was not clear but could be due to enhanced renal clearance.…”
contrasting
confidence: 56%
“…The lower plasma and CSF levels at the end of treatment in our patients are in contrast to the data of Neu et al (17) in adults in whom serum levels after multiple dosages were shown to be predictable from single-dose studies. The reason for the lower levels in our patients was not clear but could be due to enhanced renal clearance.…”
contrasting
confidence: 56%
“…The serum and sputum half-lives of cef triaxone have been reported to be approx imately 7 and 6 h, respectively, and are considerably longer than those reported for the other /?-lactam antibiotics presently in clinical use [7][8][9][10][11][12][16][17][18][19]. The clinical importance of this slow elimination is twofold: (1) the dosing interval can be ex tended to once every 24 h; (2) concentra tions achieved in serum and sputum ex ceed the minimum inhibitory concentra tions of most susceptible pathogens for up to 24 h. In addition to serum kinetics, the ability of an antibiotic to penetrate var ious tissues is an important determinant of clinical success or failure.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to a peculiar char acteristic of this molecule. Ceftriaxone is more slowly eliminated from both animals and humans than other /Mactam antibiot ics which have relatively short biological half-lifes [6][7][8][9][10][11][12],…”
mentioning
confidence: 99%
“…The higher serum levels with moxalactam may be the result of its longer half-life relative to that of cefotaxime (10,11). The serum half-life of tobra- …”
Section: Moxalactam (1-oxa-/l-lactam) and Cefotaximementioning
confidence: 99%